Pengaruh Persepsi Kemudahan, Persepsi Manfaat dan Keamanan Terhadap Minat Menggunakan E-Wallet dalam Perspektif Ekonomi Islam (Studi Pada Mahasiswa Ekonomi Islam Universitas Jambi) - Asroful Anam; Rafiqi .; Ary Dean Amry (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study examines the influence of Perceived Ease of Use, Perceived Usefulness, and Security on the Interest in Using E-Wallets from an Islamic Economics perspective. The research employs a descriptive quantitative approach, with the population consisting of undergraduate students from the Islamic Economics Study Program at Jambi University, cohorts 2021–2023. The sampling method used is simple random sampling, resulting in a total sample of 204 respondents. Data analysis was conducted using multiple linear regression with the SPSS 26 application. The results indicate that, partially, Perceived Ease of Use and Perceived Usefulness have a positive but not significant effect on the Interest in Using E-Wallets, whereas Security has a positive and significant effect. Simultaneously, the three independent variables have a significant effect on the Interest in Using E-Wallets.